Pendampingan Tata Kelola Desa Wisata Berkelanjutan Melalui Penyusunan SOP Pelayanan dan Pengelolaan Tiket di Desa Wisata Bantaragung - Susanto Susanto; Ai Nunung; Sri Purwati; Ara Aydia Van Is; Siti Marliah (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This community service activity aimed to strengthen the governance of Bantaragung Tourism Village in Majalengka through the development of service SOPs and tourism ticket management based on sustainable tourism principles. The implementation method employed an Action Participatory approach by actively involving tourism village managers in problem identification, training, mentoring, implementation, and program evaluation. The results showed an improvement in the managers’ understanding and skills related to tourism services, ticketing administration, and professional tourism governance. The preparation of service SOPs and ticket management systems contributed to improving service quality, administrative transparency, and the sustainability of tourism management. This program supports the development of a competitive and sustainable community-based tourism village.